2019
DOI: 10.4103/aer.aer_101_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between position change after low-dose spinal anesthesia and higher dose with sitting position in elderly patients: Block characteristics, hemodynamic changes, and complications

Abstract: Background:Large numbers of patients are presenting for surgeries with aging-related pre-existing conditions that make them at higher risks of adverse outcomes. Hemodynamic instability due to high sympathetic nerve block largely limits the use of conventional dose spinal anesthesia in high risk elderly patients.Aims and Objectives:We aimed to compare the hemodynamic stability and the block characteristics in low dose spinal anesthesia (5 mg) with immediate position change into supine position versus higher dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Cenkowski JM 2019 et al showed that low-dose bupivicaine group gain faster recovery of the sensory and motor blockade, early discharge, and better patient satisfaction compared to high dose bupivacaine [9]. Alsaeid et al also found that a small dose of heavy bupivacaine 0.5% (5 mg) provided better hemodynamic stability with minimal side effects in elderly patients [10]. Mehdi Sanatkar et al also showed hemodynamic stability and no ST-T changes with low dose of bupivacaine and sufentanil in patients with CAD [11].…”
Section: Discussionmentioning
confidence: 99%
“…Cenkowski JM 2019 et al showed that low-dose bupivicaine group gain faster recovery of the sensory and motor blockade, early discharge, and better patient satisfaction compared to high dose bupivacaine [9]. Alsaeid et al also found that a small dose of heavy bupivacaine 0.5% (5 mg) provided better hemodynamic stability with minimal side effects in elderly patients [10]. Mehdi Sanatkar et al also showed hemodynamic stability and no ST-T changes with low dose of bupivacaine and sufentanil in patients with CAD [11].…”
Section: Discussionmentioning
confidence: 99%
“…That is why we preferred the same doses. 13 We used very low dose heavy-bupivacaine in our study but morphine dose 0.1 mg as other studies have applied. The VAS values after 4 and 24 h were low in Group 1.…”
Section: Discussionmentioning
confidence: 99%